An Optimization Approach for Identification of Petri Nets - V. Padma; K. Bhuvaneswari (International Journal of Mathematics And its Applications, 2016)
In this paper we deal with the problem of identifying a Petri net system, given a finite language that it generates .The set of transitions and the number of places is assumed to be known. Identification problem consists in determining a Petri net system starting from example/counter example of its language. Our optimization approach requires the constraints whose set of unknowns contains the elements of the pre and post incidence matrices and the initial marking of the net. We continue to discuss the linear programming techniques for the identification of Petri nets and study their properties.